Chichén Itzá - Green, Sara, 1964- (Seven wonders of the modern world (Bellwether Media), 2021)
Presents the history, construction, design, and culture of the ancient city of Chichén Itzá in Yucatán, Mexico, one of the seven wonders of the modern world. Highlights the engineering feats of the city, and details the restoration, preservation, and protection of Chichén Itzá. Includes color photographs, fact boxes, a timeline, a glossary, and additional resources.